Importance of laparoscopic intervention in the differential diagnosis of peritonitis carcinomatosa and tuberculous peritonitis - Uyanıkoğlu, Hacer; Uyanıkoğlu, Ahmet; Büyükfırat, Evren; Gengeç, Kenan (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Uyanıkoğlu H, Uyanıkoğlu A, Büyükfırat E, Gengeç K. Importance of laparoscopic intervention in the differential diagnosis of peritonitis carcinomatosa and tuberculous peritonitis. Turk J Gastroenterol 2017; 28: 528-30.